Предмет: Алгебра, автор: dgfdgdgdfdf

Помогите плиззззззззззззззззъ

Приложения:

Ответы

Автор ответа: OblivionFire
0

Ответ:

1

Объяснение:

 \dfrac{(2 {}^{ - 3}  \times 4 {}^{2}) {}^{ - 1}  }{2 {}^{ - 1} }  =  \frac{(2 {}^{ - 3} \times (2 {}^{2}  ) {}^{2} ) {}^{ - 1} }{2 {}^{ - 1} }  =  \dfrac{(2 {}^{ - 3}  \times 2 {}^{4}) {}^{ - 1}  }{2 {}^{ - 1} }  =  \dfrac{(2 {}^{ - 3 + 4}) {}^{ - 1}  }{2 {}^{ - 1} }  =  \dfrac{(2 {}^{1}) {}^{ - 1}  }{2 {}^{ - 1} }  =  \dfrac{2 {}^{ - 1} }{2 {}^{ - 1} }  = 1.

Похожие вопросы